Pengembangan instrumen penilaian literasi matematika mahasiswa calon guru matematika - Afri, Lusi Eka; Nurrahmawati, Nurrahmawati (Jurnal Pendidik Indonesia, 2025)
Twenty-first-century learning requires teachers, particularly prospective mathematics teachers, to possess strong mathematical literacy in order to guide students in understanding, applying, and interpreting mathematics in various real-life contexts. This study aimed to develop a valid and reliable mathematical literacy assessment instrument for prospective mathematics teachers by adopting the 4-D development model. The instrument focused on counting techniques and probability concepts, aligned with the AKM/IEA mathematical literacy cognitive levels of knowing, applying, and reasoning. The trial participants consisted of 64 undergraduate students enrolled in the mathematics education program at the second, third, and fourth-year levels. Content validity analysis using Aiken’s index indicated that all items were valid, with coefficients ranging from 0.80 to 0.95. Furthermore, construct validity testing through Confirmatory Factor Analysis (CFA) demonstrated adequate convergent validity, as indicated by an Average Variance Extracted (AVE) value of 0.581 and a composite reliability (ρc) value of 0.815. These findings indicate that the developed mathematical literacy assessment instrument meets validity and reliability criteria and is therefore suitable for use as an item bank in basic statistics courses or related subjects.